Influence of Chronic Heat Acclimatization on Occupational Thermal Strain in Tropical Field Conditions. Issue 12 (December 2016) - Brearley, Matt B.; Norton, Ian; Rush, Daryl; Hutton, Michael; Smith, Steve; Ward, Linda; Fuentes, Hector
Abstract : Objective: To examine whether non-heat acclimatized (NHA) emergency responders endure greater physiological and perceptual strain than heat acclimatized (HA) counterparts in tropical field settings. Methods: Eight HA and eight NHA men urban search and rescue personnel had physiological and perceptual responses compared during the initial 4 hours shift of a simulated disaster in tropical conditions (ambient temperature 34.0 °C, 48% relative humidity, wet bulb globe temperature [WBGT] 31.4 °C). Results: From the 90th minute through to end of shift, HA (38.5 °C) sustained a significantly higher gastrointestinal temperature than NHA (38.1 °C) (mean difference 0.4 ± 0.2 °C, 95% confidence interval [CI] 0.2 to 0.7 °C, P = 0.005) despite comparable heart rate ( P = 0.30), respiratory rate ( P = 0.88), and axilla skin temperature ( P = 0.47). Overall, perception of body temperature was similar between cohorts ( P = 0.87). Conclusions: The apparent tolerance of greater physiological strain by HA responders occurred in the absence of perceptual differences.